Innovative use of micronized biomass silica-GGBS as agro-industrial by-products for the production of a sustainable high-strength geopolymer concrete - Jayanthi, V.; Avudaiappan, Siva; Amran, Mugahed; Arunachalam, Krishna Prakash; Qader, Diyar N.; Delgado, Manuel Chávez; Saavedra Flores, Erick I.; Rashid, Raizal S.M. (Elsevier BV, 2023)
Micronized biomass silica (MBS) and ground granulated blast furnace slag (GGBS) are agro-industrial byproducts generated by incinerating of rice husk (grinding in jar mill) and blast furnaces that used produce iron, respectively. MBS accounts for 20 of the world's total paddy output of 590 million tons. These by-products (MBS and GGBS) have a high concentration of amorphous silica, which is utilized as a mineral additive in concrete. This amorphous silica interacts with hydration products, resulting in the formation of additional CSH gel. This improves concrete's strength and durability properties. Therefore, it is proven that inclusion of agro-industrial by-products in concrete helps to promote sustainable and greener development, which in turn reduces carbon footprints and waste that must be disposed of in landfills. There have been few investigations on concrete using MBS and demonstrated the great potential of employing MBS as a cement substitute or additive in normal concrete. Also, the utilization of MBS as partial replace to GGBS in geopolymer concrete (GPC) with different molarity is a novel aspect of this study. However, this study has the aim and limit to develop a high-strength eco-friendly GPC with agro-industrial byproducts (MBS and GGBS) for use in sustainable construction. The impact of incorporating MBS as a partial replacement of GGBS on compressive and split tensile strengths, sorptivity, and chloride permeability was tested up to the age of 28 days. MBS was used to replace GGBS in varying percentages in the preparation of concretes. MBS were used in concrete at 0, 10, 20, and 30 replacement by weight. It was discovered that a GPC combination containing MBS 20 and the balance GGBS as the binder had the best performance in terms of its strength and durability. The compressive strengths of all GPC mixtures exceeded the intended design strength. The main findings of this study demonstrated clearly that MBS may be employed as a binder in the production of GPC.